Hierarchies, the Small Firm Effect, and Entrepreneurship: Evidence from Swedish Microdata - Joacim Tåg; Thomas Åstebro; Peter Thompson (Research Institute of Industrial Economics (IFN), 2013)
We explore whether the tendency for smaller firms to have fewer hierarchical layers explains the well-documented inverse correlation between firm size and the rate at which employees become business owners. Our analysis is based on a Swedish matched employer-employee dataset. Conditional on firm size, employees in firms with more layers are less likely to enter entrepreneurship, to become self-employed, and to switch to another employer. The effects of layers are much stronger for business creation than for jobswitching and they are stronger for entrepreneurship than for self-employment. However, hierarchies constitute only a partial explanation of the small firm effect. Potential explanations for the effects of layers are examined. Part of the effect appears to be due to preference sorting by employees, and part due to employees in firms with fewer layers having a broader range of skills.
Keywords: D20; J20; L26; M50; 330; Entrepreneurship; Employee mobility; Hierarchy; Rank; Small firm effect